Barrier film and solar cell provided with same
By using a barrier film composed of an inorganic barrier layer and a sealing layer with opposite Zeta potential in thin-film solar cells, the problem of insufficient gas barrier properties of thin-film solar cells is solved, high gas barrier properties and weather resistance are achieved, and the durability of thin-film solar cells is improved.
Patent Information
- Application Number
- CN202380091551.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-09-16
AI Technical Summary
Conventional thin-film solar cells tend to have insufficient gas barrier properties during production or after long-term use, resulting in insufficient durability.
A barrier film is used, which consists of an inorganic barrier layer and a sealing layer. The Zeta potential of the two surfaces is opposite. The sealing layer contains a two-dimensional material such as graphene or maiconene and is formed by water vapor swelling. The stacked structure optimizes the gas barrier properties.
The gas barrier and weather resistance of the barrier film are improved, ensuring the stability and durability of thin-film solar cells in long-term use.
Smart Images

Figure CN120660467A_ABST
Abstract
Description
Technical Field
[0001] Embodiments of the present invention relate to a barrier film and a solar cell including the barrier film. Background Art
[0002] In recent years, expectations for solar cells that generate electricity using sunlight have increased for environmental protection and prevention of global warming.
[0003] Conventional solar cells use relatively thick (e.g., several millimeters) glass plates as substrates and protective films. Consequently, the solar cells themselves are heavy, and their load-bearing limitations restrict the locations and equipment where they can be installed.
[0004] Therefore, in recent years, lightweight thin-film solar cells have attracted attention. Research is underway on thin-film solar cells such as thin-film silicon solar cells using Si thin films, copper-indium-gallium-selenide (CIGS)-based solar cells using CIGS thin films, copper-indium-sulfur (CIS)-based solar cells using CIS thin films, and perovskite-based solar cells using lead or tin-halogen-monovalent cation thin films. These solar cells are attracting attention as solar cells with the potential for high conversion efficiency.
[0005] Furthermore, thin-film solar cells as described above can be formed on resin films or metal films, and are therefore also called flexible thin-film solar cells. Because they are lightweight and highly flexible, flexible thin-film solar cells have fewer installation restrictions than conventional solar cells, allowing them to be freely installed on rooftops of large facilities or in locations with curved surfaces.
[0006] Furthermore, from the perspective of countermeasures against weathering degradation of battery cells, thin-film solar cells having a light-transmitting barrier film provided on the light-receiving surface side have been studied.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2019-165144 Summary of the Invention
[0010] Problems to be solved by the invention
[0011] However, the barrier films used in conventional thin-film solar cells as described above tend to have insufficient gas barrier properties during production or installation of the solar cell, or after long-term use, and further durability is desired.
[0012] An object of the present embodiment is to provide a barrier film having sufficient gas barrier properties during production, installation, and long-term use, and a solar cell including the barrier film.
[0013] Means for solving problems
[0014] According to this embodiment, the following inventions are provided.
[0015] [1] A barrier film comprising an inorganic barrier layer and a sealing layer arranged in contact with a surface of the barrier layer, wherein the sealing layer contains a two-dimensional material, and the zeta potential of the surface of the inorganic barrier layer in water at pH 6 is of opposite sign to the zeta potential of the surface of the sealing layer in water at pH 6.
[0016] [2] The barrier layer according to [1], wherein the two-dimensional material is graphene or MXene.
[0017] [3] The barrier film according to [2], wherein the graphene is graphene to which a polyalkyleneimine chain is bonded.
[0018] [4] The barrier film according to [2] or [3], wherein the graphene is nitrogen-doped graphene.
[0019] [5] The barrier film according to [2], wherein the maikoene is titanium carbide.
[0020] [6] The barrier film according to [2] or [5], wherein the maikoene contains a hydroxyl group.
[0021] [7] The barrier film according to [2], [5] or [6], wherein a nitrogen-containing compound is present on the surface of the maikoene.
[0022] [8] The barrier film according to any one of [1] to [7], wherein the sheet resistance of the sealing layer is 10 4 ~10 12 Ω.
[0023] [9] The barrier film according to any one of [1] to [8], wherein the sealing layer is formed of a two-dimensional material that swells with water vapor.
[0024]
[10] The barrier film according to any one of [1] to [9], wherein the surface of the sealing layer has a positive zeta potential in water at pH 6, and the surface of the barrier layer has a negative zeta potential in water at pH 6.
[0025]
[11] The barrier film according to any one of [1] to
[10] , wherein the sealing layer comprises a stacked structure of the two-dimensional material, and the average number of layers in the stacked structure is 2 to 6.
[0026]
[12] The barrier film according to any one of [1] to
[11] , wherein the average particle size of the two-dimensional material is 1 to 20 μm.
[0027]
[13] The barrier film according to any one of [1] to
[12] , wherein defects exist in the inorganic barrier layer.
[0028]
[14] The barrier film according to any one of [1] to
[13] , wherein the inorganic barrier layer comprises a material selected from silicon oxide, silicon nitride, silicon carbide, aluminum oxide, titanium carbide, titanium oxide, zirconium oxide, and a composite thereof.
[0029]
[15] The barrier film according to any one of [1] to
[14] , wherein the water vapor permeability of the inorganic barrier layer is 10 -3 (g / m 2 / day) or less.
[0030]
[16] The barrier film according to any one of [1] to
[15] , further comprising an additional barrier layer, wherein the barrier film has a structure in which the additional barrier layer, the inorganic barrier layer, and the sealant layer are stacked in this order.
[0031]
[17] The barrier film according to
[16] , wherein the inorganic barrier layer comprises aluminum oxide or titanium oxide, and the additional barrier layer comprises silicon oxide or silicon nitride.
[0032]
[18] The barrier film according to any one of [1] to
[17] , further comprising an additional sealing layer, wherein the barrier film has a structure in which the barrier layer, the sealing layer, and the additional sealing layer are stacked in this order.
[0033]
[19] The barrier film according to
[18] , wherein the sealing layer comprises graphene and the additional sealing layer comprises maiconene.
[0034]
[20] A solar cell comprising a light absorbing layer and the barrier film according to any one of [1] to
[19] on the light incident side of the light absorbing layer.
[0035]
[21] The solar cell according to
[20] , further comprising an ultraviolet absorbing layer.
[0036]
[22] The solar cell according to
[20] or
[21] , further comprising a transparent electrode layer between the light absorbing layer and the barrier film.
[0037]
[23] The solar cell according to any one of
[20] to
[22] , wherein the light absorbing layer contains a halogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1This is a cross-sectional view showing the barrier film according to the first embodiment.
[0039] Figure 2 It is a cross-sectional view showing a solar cell according to a second embodiment.
[0040] Figure 3 This is a cross-sectional view showing the barrier film of Example 1.
[0041] Figure 4 This is a cross-sectional view showing the barrier film of Example 2.
[0042] Figure 5 This is a cross-sectional view showing the barrier film of Example 3.
[0043] Figure 6 This is a cross-sectional view showing the barrier film of Example 4.
[0044] Figure 7 This is a cross-sectional view showing the solar cell of Example 6.
[0045] Figure 8 This is a cross-sectional view showing the solar cell of Example 7. DETAILED DESCRIPTION
[0046] Below, a barrier film according to an embodiment and a solar cell including the barrier film are described with reference to the accompanying drawings. In the following description, components having the same or similar functions are denoted by the same reference numerals. Furthermore, repeated descriptions of these components may be omitted. The accompanying drawings are schematic or conceptual, and the relationship between the thickness and width of each component, the size ratios between components, and other aspects may not necessarily correspond to actual components.
[0047] [First embodiment]
[0048] The first embodiment relates to a barrier film having high gas barrier properties and excellent weather resistance and durability due to high resistance to moisture.
[0049] Hereinafter, the configuration of the barrier film according to the present embodiment will be described.
[0050] Figure 1 1 is a conceptual cross-sectional view showing the barrier film 10 according to the first embodiment. Figure 1As shown, the barrier film 100 of the present embodiment is a composite material comprising an inorganic barrier layer 101 and a sealing layer 102 arranged in contact with the barrier layer 101. Here, the sealing layer 102 comprises a two-dimensional material. Moreover, the Zeta potential of the surface of the inorganic barrier layer 101 in water at pH 6 and the Zeta potential of the surface of the sealing layer 102 in water at pH 6 have opposite signs. The surface of the inorganic barrier layer 101 and the surface of the sealing layer 102 mentioned here strictly refer to their contact surface a, but the Zeta potential of their surfaces is the same as the Zeta potential of the surface of the material constituting the inorganic barrier layer or the sealing layer. In addition, the barrier film of the embodiment may have one or more additional barrier layers on the opposite side of the contact surface a of the inorganic barrier layer, and may have one or more additional sealing layers on the opposite side of the contact surface a of the sealing layer. Figure 1 In the embodiment, the additional barrier layer 103 and the additional sealing layer 104 are described as examples, but they may not be present. In addition, two or more additional barrier layers or additional sealing layers may be laminated.
[0051] (inorganic barrier layer and additional barrier layer)
[0052] The inorganic barrier layer 101 preferably comprises a material selected from silicon oxide, silicon nitride, silicon carbide, aluminum oxide, titanium carbide, titanium oxide, zirconium oxide, and composites thereof. The inorganic barrier layer may contain a binder material such as a polymer. In addition, the inorganic barrier layer and the polymer layer form a laminated structure, which is more flexible and therefore preferred. Furthermore, the water vapor transmission rate (WVTR) of the inorganic barrier layer is preferably low. Specifically, the WVTR is preferably 10 -3 g / m 2 / day or less, more preferably 10 -4 g / m 2 In the embodiment, WVTR is measured by the JIS Z 0208 cup method at a temperature of 40° C. and a humidity of 90%.
[0053] One or more additional barrier layers may be further laminated on the opposite side of the inorganic barrier layer's contact surface a. By using different materials for the inorganic barrier layer and the additional barrier layer, gas barrier properties, water vapor permeability, and the like can be further improved. The material for the additional barrier layer can be selected from the materials listed for the inorganic barrier layer. In particular, the use of aluminum oxide or titanium oxide as the inorganic barrier layer and silicon oxide or silicon nitride as the additional barrier layer is preferred because it allows for a robust structure and improved gas barrier properties. Furthermore, titanium oxide films have an ultraviolet light absorbing effect, thereby providing the barrier film with an ultraviolet light protection effect.
[0054] The inorganic barrier layer can be provided on a substrate (not shown). As a substrate, it can be a resin such as glass, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), etc. In the case of using glass, from the viewpoint of improving flexibility, it is preferred to use a thin film glass with a thickness of 200 μm or less. From the viewpoint of improving weather resistance and fire resistance, it is preferred to use a substrate containing a resin containing a halogen element, and the substrate can be composed only of a resin having a halogen element. As the resin constituting the substrate, it is more preferred to use a flame retardant resin having an oxygen index of 22% or more, for example, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), silicone resin, polyvinylidene fluoride (PVDF), polyimide (PI) and polycarbonate (PC). By using them as a substrate, a barrier film having excellent flexibility and excellent weather resistance and fire resistance and a solar cell having the barrier film can be obtained. In addition, the substrate can also be a composite material formed by combining multiple components.
[0055] The film thickness of the substrate is not particularly limited, but as a resin substrate, it can be set in the range of 10 to 200 μm from the viewpoint of handling. The film thickness of the substrate is preferably 30 to 150 μm.
[0056] (Sealing layer and additional sealing layer)
[0057] In an embodiment, the sealing layer includes a two-dimensional material. The two-dimensional material is a layered compound that is bonded by a strong intralayer covalent bond and a weak interlayer van der Waals force. As such two-dimensional materials, there are graphene, single element structures (phosphorene, stanene, silicene, germanene) and binary compounds (boron nitride, transition metal dichalcogenide (TMD: transition metaldichalcogenide), etc.), clay, two-dimensional carbides known as MXene, nitrides and carbonitrides. The material of the sealing layer can be arbitrarily selected from these two-dimensional materials according to the purpose, among which graphene or MXene is preferably used. The conductivity of these materials is high enough to obtain an antistatic effect, so it can prevent the adhesion of impurities, etc., and therefore is preferred. In addition, graphene has high gas barrier properties and is therefore preferred.
[0058] Graphene has a skeleton composed of carbon atoms bonded in a planar shape, and is preferably chemically modified. One preferred graphene is polyalkyleneimine represented by the following formula, particularly graphene having a structure bonded with polyethyleneimine chains.
[0059] [Chemical Formula 1]
[0060]
[0061] Graphene with such a structure improves its water dispersibility, facilitating coating when forming a film by coating, and enabling a positive zeta potential. When silicon oxide or silicon nitride is used in an inorganic barrier film, these materials have negative zeta potentials, improving the adhesion between the inorganic barrier layer and the sealing layer. Therefore, graphene preferably has a structure with polyethyleneimine chains bonded thereto.
[0062] In the formula, a polyethyleneimine chain is exemplified as the polyalkyleneimine chain, but n is not particularly limited, and preferably n = 2 to 8, particularly preferably polyethyleneimine with n = 2. Furthermore, not only linear polyalkyleneimines but also polyalkyleneimines having branched or cyclic structures can be used.
[0063] In addition, it is also preferable that part of the carbon atoms in the graphene skeleton be substituted with nitrogen. By substituting part of the carbon atoms constituting graphene with nitrogen, ion adsorption can be improved.
[0064] In addition, maikoene is represented by the general formula: M n+1 X n T x Represented. In the formula, M is an early transition metal such as Ti, V, Nb, X is C or N, and T is a terminal group such as -OH, -O, -Cl. Among them, titanium carbide in which M is Ti and X is C is preferred. By using titanium carbide, improvements in conductivity, barrier properties and fire resistance can be expected. Moreover, it is preferred that T is -OH and contains hydroxyl groups. Since the maikoene having hydroxyl groups has high water dispersibility, it is advantageous in the case of forming a sealing layer by coating, and surface modification becomes easy, so it is preferred. Such maikoene having hydroxyl groups is easy to maintain the stacking structure of the maikoene particles through interlayer hydrogen bonds, so it is preferred. In addition, when there is a nitrogen-containing compound on the surface of the maikoene particles, the Zeta potential of the maikoene can be made positive, or it can easily adsorb ions, so it is preferred.
[0065] Furthermore, one or more additional sealing layers may be further laminated on the opposite side of the sealing layer from the contact surface a. Using different materials for the sealing layer and the additional sealing layer can further improve gas barrier properties, water vapor permeability, and the like. The material for the additional sealing layer can be selected from the materials listed above for the sealing layer. In particular, using graphene as the sealing layer and maiconene as the additional sealing layer is preferred because it improves gas barrier properties.
[0066] Furthermore, if the sealing layer is formed from a two-dimensional material that swells with water vapor, the two-dimensional material swells upon contact with water vapor, narrowing the spacing between particles and thus tending to reduce the water vapor permeability. Therefore, it is preferable that the sealing layer be formed from a two-dimensional material that swells with water vapor.
[0067] Furthermore, it is preferred that the sealing layer include a laminated structure of a two-dimensional material, and the average number of layers in the laminated structure is 2 to 6. By setting the average number of layers within this range, both excellent gas barrier properties and excellent transparency can be achieved.
[0068] Furthermore, the sheet resistance of the sealing layer is preferably 10 4 ~10 12 Ω, more preferably 10 4 ~10 8 Ω.
[0069] The sealing layer 102 comprises the above-mentioned two-dimensional material, but can also be a layer further compounded with an adhesive such as a resin. As the adhesive, preferably silicone resin, epoxy resin, olefin resin, etc. As the adhesive polymer, preferably a polymer that dissolves or disperses in a solvent dispersion of the two-dimensional material. Preferably, it is transparent and waterproof after coating and drying. When the zeta potential of the adhesive polymer in water at pH 6 is the same as that of the two-dimensional material, the dispersibility is good, so it is preferred.
[0070] The defect-free portions of two-dimensional materials have excellent gas barrier properties, making them suitable for forming sealing layers. Furthermore, particles with a high aspect ratio, specifically micrometer-order widths and nanometer-order thicknesses, can be easily formed into flexible sealing layers over large areas by applying a dispersion of these particles.
[0071] The average particle size of the two-dimensional material in the width direction is preferably 1 to 20 μm. This makes it easier to seal defects in the barrier layer. When the average particle size is less than 1 μm, the barrier properties tend to decrease, and when it is greater than 20 μm, it tends to be difficult to disperse in water, so care should be taken. The average particle size is preferably 5 to 10 μm. It should be noted that, in the embodiment, the average particle size of the two-dimensional material particles can be measured by observing a coated dry film containing the two-dimensional material using a SEM.
[0072] (Lamination of Inorganic Barrier Layer and Sealant Layer)
[0073] While the inorganic barrier layer 101 has high gas barrier properties when it is free of defects, cracks may form when bent or subjected to impact, reducing its barrier properties. Furthermore, in solar cells and the like, impurities are easily introduced during manufacturing, and cracks are also easily generated during handling when a large area is required.
[0074] Here, by stacking the inorganic barrier layer 101 and the sealing layer 102, particles of the two-dimensional material are arranged on the defects present in the inorganic barrier layer 101 to seal the defects, thereby improving the gas barrier properties. In this case, by stacking the particles of the two-dimensional compound in two or more layers, the probability of sealing the defects is increased, and the gas barrier properties can be further improved. Even if there are no defects in the inorganic barrier layer 101, the particles of the two-dimensional material are bound to the surface of the inorganic barrier layer by stacking the sealing layer 102, so even if stress is applied during processing, the inorganic barrier layer is less likely to have defects. In addition, even if defects are generated in the inorganic barrier layer during processing, the effect of sealing the defects can be exerted when the defects are formed directly below the particles of the two-dimensional material. If the film thickness of the sealing layer is thickened, it is difficult for water vapor and the like to pass through the barrier film because the movement distance becomes longer. However, if the film thickness becomes too thick, the light transmittance sometimes becomes insufficient, so it is preferred to adjust the film thickness appropriately.
[0075] (Effect of Zeta Potential)
[0076] By making the surface of the inorganic barrier layer 101 and the surface of the sealing layer 102 have Zeta potentials of opposite signs in water at pH 6, the adhesion between the inorganic barrier layer 101 and the sealing layer 102 is increased, and it is not easy to peel off. In addition, the two-dimensional material can easily invade the defects of the inorganic barrier layer, which can easily prevent the reduction of barrier performance. For example, when solar cells are arranged in an external environment, most solar cells are exposed to weakly acidic rain containing carbon dioxide, etc., so it is important to focus on the Zeta potential in water at pH 6. Preferably, the Zeta potential of the surface of the above-mentioned sealing layer in water at pH 6 is positive, and the Zeta potential of the surface of the above-mentioned barrier layer in water at pH 6 is negative.
[0077] The zeta potential in water usually changes when the pH changes, but it is not easy to change drastically. Generally, when the pH increases, the zeta potential changes from positive to negative. The isoelectric point where the potential is 0 varies depending on the material. The isoelectric point of silicon oxides or polymers with carboxylic acid groups, where protons are easily dissociated, is in the low pH (acidic) region, and the isoelectric point of compounds with alkaline amine groups is in the high pH (alkaline) region. The isoelectric point of polymers with carbonyl groups in polymers is in the acidic region, and most of them have a negative zeta potential at pH 6. The isoelectric points of titanium oxides, aluminum oxides, and silicon nitrides are in the neutral or alkaline region, and usually have a positive zeta potential at pH 6. Two-dimensional compounds such as graphene, maicoene, and clay usually have a negative zeta potential at pH 6. These zeta potentials can be changed by surface modification of each material. For example, a surface treatment agent with an amino group can be used to make the zeta potential positive, or a surface treatment agent with a carboxylic acid group can be used to make the zeta potential negative.
[0078] A strong barrier film can be formed by stacking a layer of aluminum oxide or titanium oxide with a positive zeta potential (barrier layer) on silicon oxide with a negative zeta potential (additional barrier layer), stacking a layer of maiconene with a negative zeta potential (sealing layer) on it, and then stacking a layer of graphene bonded with polyethyleneimine chains with a positive zeta potential (additional sealing layer) on it.
[0079] It should be noted that the zeta potential of a flat sample surface can be measured by electrophoretic light scattering (ELS) using a Zetasizer Nano ZS (manufactured by Malvern). Specifically, the measurement is performed using a flat plate zeta potential measurement cell and polystyrene latex as tracer particles. The pH during the zeta potential measurement can be adjusted by adding dilute hydrochloric acid and a dilute potassium hydroxide aqueous solution to pure water.
[0080] Similarly, for powdered samples, the zeta potential of the object to be measured can be measured by electrophoretic light scattering (ELS) using a "Zetasizer Nano ZS" (manufactured by Malvern). The sample cell used in this case is a capillary sample cell.
[0081] The zeta potential of each material at the interface between the inorganic barrier layer, additional barrier layer, sealant layer, and additional sealant layer can be evaluated using a flat plate sample, as long as each can be delaminated at the interface. Alternatively, separate flat plate samples and powdered samples containing the respective materials can be used for evaluation.
[0082] The barrier film may further include a UV absorbing layer. Using titanium oxide in the barrier layer can provide a UV absorbing effect. Furthermore, by laminating the UV absorbing layer containing a UV absorber on, for example, a sealing layer or an additional sealing layer, light resistance can be further improved.
[0083] Furthermore, a transparent electrode layer may be provided on the side of the barrier layer opposite to the sealing layer, thereby reducing the number of components when manufacturing a device such as a solar cell.
[0084] These auxiliary layers may be embedded not only in the barrier film of the embodiment but also in a device such as a solar cell including the barrier film.
[0085] The barrier film 100 according to the first embodiment has been described above.
[0086] According to the barrier film 100 according to the first embodiment, it is possible to provide a flexible barrier film that is excellent in gas barrier properties and weather resistance and has high durability.
[0087] [Second embodiment]
[0088] The second embodiment relates to a solar cell 200 including the barrier film of the first embodiment. The solar cell of the second embodiment can be formed by arbitrarily combining conventionally known structures in addition to the barrier film of the first embodiment.
[0089] like Figure 2 As shown, the solar cell 200 of the embodiment includes the barrier film 100 of the first embodiment on the light incident side and further includes a power generation unit 201 below the barrier film 100. It is preferable to use a power generation unit using a halogen-containing perovskite compound in the light absorption layer of the power generation unit 201 because the performance of the barrier film 100 can be most effectively utilized.
[0090] <Solar Cell Power Generation Unit>
[0091] The solar cell power generation section 201 includes, in order from the side opposite the light-receiving surface, a substrate 202, a first electrode 203, a light-absorbing layer 204, and a second electrode 205. Furthermore, interlayers (not shown) (e.g., a hole transport layer and an electron injection layer) may be included between the first electrode 203 and the light-absorbing layer 204, and between the light-absorbing layer 204 and the second electrode 205. Furthermore, a protective layer (not shown) or another substrate may be provided on the first electrode 203 and the second electrode 205 (i.e., between the first electrode 203 and the substrate 202, and between the second electrode 205 and the barrier film 100).
[0092] The solar cell power generation section will be described in detail below.
[0093] (Substrate)
[0094] The substrate 202 is not particularly limited. To ensure flexibility, resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyvinyl chloride (PVC), polycarbonate (PC), polyvinylidene fluoride (PVDF), polyvinylidene chloride (PVDC), polyimide, acrylic acid, aluminum foil, and stainless steel foil are preferably used. The thickness of the substrate 1 is, for example, 50 μm to 200 μm.
[0095] (First Electrode)
[0096] The first electrode 203 may be a metal film or a transparent electrode. In the case of a transparent electrode, a laminated film is preferred. For example, a transparent conductive oxide film primarily composed of Sn is preferably provided as the first layer on the light-absorbing layer 204 side, and a transparent conductive film having a lower resistance than the first layer is provided as the second layer on the substrate 202 side. The laminated film is preferred because the transparent conductive oxide film primarily composed of Sn as the first layer has a higher resistivity than the second layer. Therefore, if the first layer is used alone, power generation losses due to the resistance component are significant.
[0097] The first layer is preferably an oxide containing Sn as a main component, such as SnO2. If necessary, the first layer may contain an additive. The additive is not limited, and examples thereof include Zn, Al, Ga, In, Si, Ge, Ti, Cu, Sb, Nb, F, and Ta.
[0098] As the second layer, for example, indium tin oxide (ITO), aluminum-doped zinc oxide (AZO), boron-doped zinc oxide (BZO), gallium-doped zinc oxide (GZO), indium-doped zinc oxide (IZO), titanium-doped indium oxide (ITiO), indium gallium zinc oxide (IGZO), hydrogen-doped indium oxide (In2O3), etc. can be used, without particular limitation. The transparent conductive film can be a laminated film, and in addition to the above-mentioned oxides, the laminated film can also contain a film of tin oxide, etc. In addition, the first electrode 203 can also use an electrode in which a transparent conductive film and a metal film are laminated. By setting the metal film to a thickness of 4 nm to 20 nm, it can be used as a transparent electrode. The transparent conductive film is as described above, but the metal film may be a film of Al, Ag, stainless steel, Mo, Au, or W, etc., without particular limitation.
[0099] The first electrode can be a carbon-containing film (carbon nanotubes, graphene, graphite, etc.). These films are highly stable and have high tolerance to humidity and halogens. However, since they have higher resistance than metal films, it is preferable to add a metal auxiliary electrode.
[0100] The first electrode 203 is formed by vacuum deposition, sputtering, ion plating, plating, coating, or the like. The thickness of the first electrode 203 can be appropriately determined depending on the material used, and is preferably 50 nm to 250 nm, for example. In the case of a carbon electrode, the thickness of the first electrode is preferably 10 μm to 50 μm.
[0101] (Light absorbing layer)
[0102] The light absorbing layer 204 is not particularly limited as long as it is a layer electrified by incident sunlight, and a material having a perovskite structure (perovskite compound) can be used, preferably a perovskite compound containing a halogen element.
[0103] For example, a perovskite structure is composed of ions A1, A2, and X, and can be expressed as A1A2X3. When ions A2 are smaller than ions A1, a perovskite structure may be formed. For example, a perovskite structure has a cubic unit cell. Ions A1 are located at each vertex of the cubic crystal, and ions A2 are located at the body center. Ions X are located at the face centers of the cubic crystal, centered around ions A2.
[0104] The orientation of the A2X6 octahedron is easily deformed due to the interaction with the ion A1. Due to the reduction of symmetry, a Mott transition occurs, and the valence electrons locally present in the ion M can serve as an energy band expansion. The ion A1 is preferably CH3NH3 + Ion A2 is preferably Pb 2+ and Sn 2+ Ion X is preferably Cl - Br - and I - The materials constituting the ions A1, A2, and X may be either a single material or a mixture of materials. The thickness of the light absorbing layer 204 is, for example, 200 nm to 800 nm.
[0105] When forming the light absorbing layer 204, it is preferred to adopt a coating method in which the material is dissolved in a solvent and applied to the electrode (or intermediate layer). According to the coating method, a large-area light absorbing layer can be easily formed. As the solvent used, for example, unsaturated hydrocarbon solvents, halogenated aromatic hydrocarbon solvents, halogenated saturated hydrocarbon solvents, ethers, etc. can be listed. As unsaturated hydrocarbon solvents, toluene, xylene, tetralin, decalin, mesitylene, n-butylbenzene, sec-butylbenzene, tert-butylbenzene, etc. can be listed. As halogenated aromatic hydrocarbon solvents, chlorobenzene, dichlorobenzene, trichlorobenzene, etc. can be listed. As halogenated saturated hydrocarbon solvents, carbon tetrachloride, chloroform, dichloromethane, dichloroethane, chlorobutane, bromobutane, chloropentane, chlorohexane, bromohexane, chlorocyclohexane, etc. can be listed. As ethers, tetrahydrofuran, tetrahydropyran, etc. can be listed. It is more preferred to use a halogen-based aromatic solvent. Furthermore, DMF (N,N-dimethylformamide), DMSO (dimethyl sulfoxide), 2-propanol, and γ-butyrolactone can also be used. These solvents can be used alone or in combination. There are no particular restrictions on the solvent as long as it can dissolve the material and does not damage it.
[0106] Examples of methods for applying the solution include spin coating, dip coating, casting, rod coating, roll coating, wire bar coating, spraying, screen printing, gravure printing, flexographic printing, offset printing, gravure / offset printing, dispenser coating, nozzle coating, capillary coating, inkjet coating, and meniscus coating. These coating methods may be used alone or in combination.
[0107] (Second Electrode)
[0108] The second electrode 205 preferably includes a transparent conductive material. In this embodiment, the second electrode 205 can be made of the same material as the first electrode 203. Like the first electrode 203, the second electrode 205 can be formed by vacuum deposition, sputtering, ion plating, electroplating, coating, or the like.
[0109] The structure of the solar cell 200 according to the second embodiment has been described above.
[0110] According to the solar cell 200 of the second embodiment, by including the first embodiment having excellent gas barrier properties, it is possible to provide a flexible thin-film solar cell having excellent weather resistance and fire resistance and high durability.
[0111] Furthermore, the configuration, thickness, composition, and the like of each layer constituting the solar cell 200 of the second embodiment can be appropriately changed within a range that does not impair the above-described effects.
[0112] Furthermore, as described above, a protective film or the like may be provided between the solar cell power generation section 201 and the barrier film 100 , or the solar cell power generation section 201 and the barrier film 100 may be in direct contact with each other.
[0113] According to at least the second embodiment described above, a solar cell having excellent weather resistance and durability can be provided.
[0114] Example
[0115] The present embodiment will be described in more detail below using examples. However, the conditions in the examples are merely examples adopted to confirm the feasibility and effectiveness of the present embodiment, and the present embodiment is not limited to these conditional examples. Various conditions can be adopted in the present embodiment as long as they do not deviate from the main purpose of the present embodiment and achieve the purpose of the present embodiment.
[0116] (Example 1)
[0117] Production with Figure 3 The barrier film 300 has the structure shown.
[0118] First, a 100 μm thick polycarbonate (PC) film was prepared as a substrate 301. Sputtering was performed three times on the surface of the substrate 301 to form a 100 nm thick barrier layer 302 made of a silicon oxide film. The silicon oxide film 302 has a negative zeta potential in water at pH 6.
[0119] Next, a 0.05 wt% aqueous dispersion of single-layer graphene with polyethyleneimine chains bonded thereto was applied onto the barrier layer 302 to form a sealing layer 303 composed of a graphene film with a thickness of approximately 2 nm. Based on the absorbance, the graphene film consisted of approximately three layers on average. The graphene film had a positive zeta potential in water at pH 6.
[0120] For the obtained barrier film 300, the WVTR was 4×10 -3 g / m 2 / day, with excellent barrier properties, even with a 5mm diameter glass rod subjected to 100 bending tests, the WVTR increased by 10%.
[0121] (Comparative Example 1)
[0122] A barrier film was produced in the same manner as in Example 1 except that the graphene film was not formed.
[0123] The WVTR of the barrier film is 9×10 -2 g / m 2 / day barrier properties, if a 5mm diameter glass rod is used for 100 bending tests, the WVTR increases to 3×10 -1 g / m 2 / sky.
[0124] (Example 2)
[0125] Production with Figure 4 The barrier film 400 has the structure shown.
[0126] First, a 60 μm thick polycarbonate (PC) film was prepared as a substrate 401, and a 200 nm thick barrier layer 402 made of a silicon nitride film was formed by CVD on the surface of the substrate 401. The barrier layer 402 had a positive zeta potential in water at pH 6.
[0127] Next, a 0.01 wt% aqueous dispersion of a single layer of maicone (titanium carbide) having a negative zeta potential and hydroxyl groups on its surface in water at pH 6 is applied on the barrier layer 402 to laminate a sealing layer 403 made of maicone with a thickness of about 2 nm.
[0128] For the obtained barrier film 400, the WVTR was 5×10 -3 g / m 2 / day, with excellent barrier properties, even with a 5mm diameter glass rod subjected to 100 bending tests, the WVTR increased by 8%.
[0129] Comparative Example 2
[0130] A barrier film was prepared in the same manner as in Example 2, except that a 0.05 wt% aqueous dispersion of a single-layer graphene with positive zeta potential and bonded polyethyleneimine chains in water at pH 6 was applied instead of maicoene to prepare a sealing layer consisting of a graphene film with a thickness of about 2 nm.
[0131] The WVTR of the barrier film is 6×10 -3 g / m 2 / day barrier properties, if a 5mm diameter glass rod is used for 100 bending tests, the WVTR increases to 2×10 -2 g / m 2 / sky.
[0132] (Example 3)
[0133] Production with Figure 5 The barrier film 500 has the structure shown.
[0134] First, a 50 μm thick polyvinylidene fluoride (PVDF) film was prepared as a substrate 501. A 0.5 w% hexane solution of polysilazane was applied to the surface of the substrate 501. This produced a barrier layer 54 consisting of a silicon oxide film 502 near the surface and a silicon nitride film 503 inside.
[0135] Next, a 0.05 wt % aqueous dispersion of a single-layer graphene bonded with polyethyleneimine chains was applied onto the silicon oxide film 502 to form a sealing layer 505 composed of a graphene film having a thickness of approximately 2 nm.
[0136] For the obtained barrier film 500, the WVTR was 6×10 -4 g / m 2 / day, with excellent barrier properties, even with a 5mm diameter glass rod subjected to 100 bending tests, the WVTR increased by 10%.
[0137] (Example 4)
[0138] Production with Figure 6 The barrier film 600 is of the structure shown.
[0139] First, a 100 μm thick polyethylene terephthalate (PET) film was prepared as a substrate 601, and a 150 nm thick crystalline ITO film 602 was formed on the back surface. A 100 nm thick silicon oxide film 603 was formed on the surface of this substrate 601 by sputtering three times. A 50 nm thick titanium oxide film 604 was formed on top of this by sputtering twice to form a barrier layer 605. The zeta potential of titanium oxide 603 in water at pH 6 is positive. The titanium oxide film also serves as an ultraviolet light absorbing layer.
[0140] Next, a 0.01 wt% aqueous dispersion of a single layer of maicone (titanium carbide) having a hydroxyl group on its surface is applied on the barrier layer 605 to form a sealing layer 606 composed of maicone with a thickness of about 2 nm.
[0141] The WVTR of the obtained barrier film 60 was 2×10 -4 g / m 2 / day, with excellent barrier properties, even with a 5mm diameter glass rod subjected to 100 bending tests, the WVTR increased by 10%.
[0142] (Example 5)
[0143] A barrier film was produced in the same manner as in Example 4, except that aluminum oxide was used instead of the titanium oxide film. The zeta potential of aluminum oxide in water at pH 6 is positive.
[0144] For the obtained barrier film, the WVTR was 5×10 -4 g / m 2 / day, has excellent barrier properties, and even when a 100-fold bending test is performed using a 5mm diameter glass rod, the WVTR increases by 15%.
[0145] (Example 6)
[0146] Production Figure 7 A solar cell (solar cell) 700 is shown.
[0147] A transparent electrode (second electrode) 72 made of indium tin oxide (ITO) (200 nm) was formed on a 100 μm thick PC film (substrate 701) with a hard coating by sputtering. C was applied to the transparent electrode 702 using a bar coater. 60 -PCBM toluene solution and dried to form the electron injection layer 703.
[0148] Next, a solution of lead iodide and methylammonium iodide dissolved in a solvent was applied onto the electron injection layer 73 and dried to form the light absorption layer 74. Next, a solution of 2,2',7,7'-tetrakis[N,N-bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene (hereinafter referred to as Spiro-OMeTAD) was applied onto the light absorption layer 704 and dried to form the hole transport layer 705.
[0149] Next, a counter electrode (first electrode) 76 made of molybdenum (Mo) was formed on the hole transport layer 705 by sputtering.
[0150] The barrier film 300 obtained in Example 2 was attached to the surface of a PC substrate 701 opposite to the transparent electrode (second electrode) 702 (i.e., the light-receiving side). A silicone gel sealant 707 was applied thereto, and a protective film (PVDF film) 708 was attached. A silicone gel sealant 709 was applied to the first electrode (Mo electrode) 706, and aluminum foil 710 was attached to fabricate a solar cell 700. The periphery of the element was also sealed with a sealant and aluminum foil (not shown).
[0151] The resulting solar cell 700 exhibited an energy conversion efficiency of approximately 12% for 1 sun of sunlight. Even after 100 bends using a 5 mm diameter glass rod, the efficiency dropped by only 5%. Furthermore, even after 1000 hours at 85% humidity and 85°C, the efficiency dropped by only 10%.
[0152] (Example 7)
[0153] Production Figure 8 A solar cell (solar cell) 800 is shown.
[0154] An electron injection layer 802 made of tin oxide was formed by sputtering on the ITO transparent electrode (second electrode) of the barrier film 600 obtained in Example 4. Next, a solution of lead iodide and methylammonium iodide dissolved in a solvent was applied to the electron injection layer 801 and dried to form a light absorption layer 802. Next, a solution of Spiro-OMeTAD was applied to the light absorption layer 802 and dried to form a hole transport layer 803.
[0155] Next, an Au electrode (first electrode) 804 is formed by vapor deposition on the hole transport layer 803. A silicone gel sealant 805 is applied to the barrier film, followed by a protective film (PVDF film) 806. A silicone gel sealant 807 is applied to the Au electrode, followed by an aluminum foil 808, to complete the solar cell 800. The periphery of the element is also sealed with a sealant and aluminum foil (not shown).
[0156] The resulting solar cell 800 exhibited an energy conversion efficiency of approximately 14% for 1sun of sunlight. Even after 100 bends using a 5mm diameter glass rod, the efficiency dropped by only 5%. Furthermore, even after 1000 hours at 85% humidity and 85°C, the efficiency dropped by only 8%.
[0157] While several embodiments of the acid component removal apparatus and method of the present invention have been described above, these embodiments are provided as examples and do not limit the scope of the invention. These embodiments may be implemented in various other forms, and various omissions, substitutions, modifications, and additions may be made without departing from the spirit of the invention. These embodiments and their variations are intended to be included within the scope and spirit of the invention and within the scope of the invention set forth in the claims and their equivalents.
[0158] Description of Reference Numerals
[0159] 100, 300, 400, 500, 600...barrier film,
[0160] 200, 700, 800... solar cells,
[0161] 101, 302, 504, 605... barrier layer,
[0162] 102, 303, 606…sealing layer,
[0163] 103, 104 ... contact surface,
[0164] 105, 301, 401, 501, 601…base material,
[0165] 201…Solar cell power generation unit,
[0166] 202,701…substrate,
[0167] 203, 706, 804…first electrode,
[0168] 204, 704, 802…light absorption layer,
[0169] 205, 702 ... second electrode,
[0170] 502, 603...silicon oxide film,
[0171] 503…Silicon nitride film,
[0172] 604...Titanium oxide film,
[0173] 703, 801... electron injection layer,
[0174] 705, 803 ... hole transport layer,
[0175] 602…Crystalline ITO film,
[0176] 707, 709, 805, 807…sealing materials,
[0177] 708, 806... protective film,
[0178] 710, 808…aluminum foil
Claims
1. A barrier film comprising an inorganic barrier layer and a sealing layer arranged in contact with a surface of the barrier layer, The sealing layer contains a two-dimensional material, The Zeta potential of the surface of the inorganic barrier layer in water with a pH of 6 is of opposite sign to the Zeta potential of the surface of the sealing layer in water with a pH of 6.
2. The barrier layer according to claim 1, wherein The two-dimensional material is graphene or maiconene.
3. The barrier film according to claim 2, wherein The graphene is graphene bonded with a polyalkyleneimine chain.
4. The barrier film according to claim 2, wherein The graphene is nitrogen-doped graphene.
5. The barrier film according to claim 2, wherein The maikeene is titanium carbide.
6. The barrier film according to claim 2, wherein The maikoene contains hydroxyl groups.
7. The barrier film according to claim 2, wherein There is a nitrogen-containing compound on the surface of the maikoene.
8. The barrier film according to claim 1 or 2, wherein The sheet resistance of the sealing layer is 10 4 ~10 12 Ω.
9. The barrier film according to claim 1 or 2, wherein The sealing layer is formed of a two-dimensional material that swells with water vapor.
10. The barrier film according to claim 1 or 2, wherein The Zeta potential of the surface of the sealing layer in water with a pH of 6 is positive, and the Zeta potential of the surface of the barrier layer in water with a pH of 6 is negative.
11. The barrier film according to claim 1 or 2, wherein The sealing layer comprises a stacked structure of the two-dimensional material, and the average number of layers of the stacked structure is 2 to 6.
12. The barrier film according to claim 1 or 2, wherein The average particle size of the two-dimensional material is 1 to 20 μm.
13. The barrier film according to claim 1 or 2, wherein Defects exist in the inorganic barrier layer.
14. The barrier film according to claim 1 or 2, wherein The inorganic barrier layer includes a material selected from the group consisting of silicon oxide, silicon nitride, silicon carbide, aluminum oxide, titanium carbide, titanium oxide, zirconium oxide, and composites thereof.
15. The barrier film according to claim 1 or 2, wherein The water vapor permeability of the inorganic barrier layer is 10 -3 (g / m 2 / day) or less.
16. The barrier film according to claim 1 or 2, wherein The barrier film further includes an additional barrier layer, and has a structure in which the additional barrier layer, the inorganic barrier layer, and the sealant layer are stacked in this order.
17. The barrier film according to claim 16, wherein The inorganic barrier layer comprises aluminum oxide or titanium oxide, and the additional barrier layer comprises silicon oxide or silicon nitride.
18. The barrier film according to claim 1 or 2, wherein The barrier film further includes an additional sealing layer, and has a structure in which the barrier layer, the sealing layer, and the additional sealing layer are stacked in this order.
19. The barrier film according to claim 18, wherein The sealing layer comprises graphene, and the additional sealing layer comprises maiconene. 20 . A solar cell comprising a light-absorbing layer and the barrier film according to claim 1 or 2 on the light-incident side of the light-absorbing layer.
21. The solar cell according to claim 20, wherein The solar cell further includes an ultraviolet absorbing layer.
22. The solar cell according to claim 20, wherein A transparent electrode layer is provided between the light absorbing layer and the barrier film.
23. The solar cell according to claim 20, wherein The light absorbing layer contains halogen.
Citation Information
Patent Citations
Solar cell
JP2019165144A